Classification and genomic diversity of enterically transmitted hepatitis viruses - Smith, D; Simmonds, P (Cold Spring Harbor Laboratory Press, 2018)
Hepatitis A virus (HAV) and hepatitis E virus (HEV) are significant human pathogens and are responsible for a substantial proportion of cases of severe acute hepatitis worldwide. Genetically, both viruses are heterogeneous and are classified into several genotypes that differ in their geographical distribution and risk group association. There is, however, little evidence that variants of HAV or HEV differ antigenically or in their propensity to cause severe disease. Genetically more divergent but primarily hepatotropic variants of both HAV and HEV have been found in several mammalian species, those of HAV being classified into eight species within the genus Hepatovirus in the virus family Picornaviridae. HEV is classified as a member of the species Orthohepevirus A in the virus family Hepeviridae, a species that additionally contains viruses infecting pigs, rabbits, and a variety of other mammalian species. Other species (Orthohepevirus B–D) infect a wide range of other mammalian species including rodents and bats.